2013
DOI: 10.1590/1516-4446-2012-1048
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Beck Depression Inventory-II: a comprehensive review

Abstract: Objective: To review the psychometric properties of the Beck Depression Inventory-II (BDI-II) as a self-report measure of depression in a variety of settings and populations. Methods: Relevant studies of the BDI-II were retrieved through a search of electronic databases, a hand search, and contact with authors. Retained studies (k = 118) were allocated into three groups: non-clinical, psychiatric/institutionalized, and medical samples. Results: The internal consistency was described as around 0.9 and the retes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
765
1
36

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,121 publications
(886 citation statements)
references
References 133 publications
(101 reference statements)
21
765
1
36
Order By: Relevance
“…70,71 Estimates of sensitivity, specificity, and NPV for the BDI-II from studies included in this review are in line with those found in other studies, 72 with PPV estimates from included studies in this review near the lower range but generally consistent with PPV estimates produced in other medical samples. The GDS, HADS, and PHQ did not have uniform versions (i.e., they differed in either items assessed or cutpoint used) employed in more than two studies in the present review, limiting comparability with other research, though in general the reported metrics from presently included studies appear broadly consistent with those reported from studies that have examined these measures in other non-post-ACS populations.…”
Section: Depression Screening Properties In Post-acs Patientssupporting
confidence: 88%
“…70,71 Estimates of sensitivity, specificity, and NPV for the BDI-II from studies included in this review are in line with those found in other studies, 72 with PPV estimates from included studies in this review near the lower range but generally consistent with PPV estimates produced in other medical samples. The GDS, HADS, and PHQ did not have uniform versions (i.e., they differed in either items assessed or cutpoint used) employed in more than two studies in the present review, limiting comparability with other research, though in general the reported metrics from presently included studies appear broadly consistent with those reported from studies that have examined these measures in other non-post-ACS populations.…”
Section: Depression Screening Properties In Post-acs Patientssupporting
confidence: 88%
“…Scores are generally classified as the following: 0-13, minimal or no depression; 14-19, mild depression; 20-28, moderate depression; and 29-63, severe depression. 14,15 Subfactor analysis was performed to determine the impact of CRS on somatic and cognitive subdomains. 15,16 …”
Section: Demographics Comorbidities and Disease Severitymentioning
confidence: 99%
“…One of the trials used the newer BDI-II version. Since the 2 versions are highly correlated (r = 0.82-0.94) and have an identical point range, we used them as one scale (BDI) [21]. All studies used the same Clinical Severity Score for Glabellar Frown Lines (CSS-GFL) to assess frown scores at baseline and week 6 [22].…”
Section: Inclusion Criteria Scales and Data Poolingmentioning
confidence: 99%